Dynamic Voltage Restorer for Sag and Swell Issues in Power System - Lakshmi Lakshmi Kumari; Uma Vani Uma Vani (Institute of Advanced Engineering and Science, 2018)
This paper presents the application of dynamic voltage restorers (DVR) on power distribution Systems for mitigation of voltage sags/swells at critical loads. DVR is one of the compensating types of custom power devices. The power quality is affected mainly due to the sensitive loads which results in voltage sag and voltage swells. It is necessary to investigate the suitable methods for mitigation of voltage sags. Sensitivity is the main cause of the above power quality problems and it cannot be eliminated completely as it has many other operating properties. So the next possible solution is to correct the problems caused by the sensitive equipments connected to the faulty loads. The occurrence of sag and swell varies with equipment, environment, process operations, desired control schemes etc. From the wide range of mitigation methods, the selected one has to be observed for the effect on the characteristics. These problems can be mitigated with voltage injection method using custom power device, Dynamic Voltage Restorer (DVR). In this paper we design a Dynamic Voltage Restorer (DVR) which is utilized for power quality improvement. The main power quality problems like voltage sag and swell are studied in this paper. The device used to phase out voltage sags and a swell in the distribution lines is the Dynamic Voltage Restorer (DVR). The Dynamic Voltage Restorer is a special type of power device used for providing consistent and reliable supply power to the load devices. Dynamic Voltage Restorer uses a vector control strategy for mitigating power quality problems by automatically detecting and injecting the voltage components through an injection transformer. Here comes the importance of soft computing techniques like PI controller. The system will be able to correct repeated occurrences of the power quality problems.